Culture and partner violence: examining loss of face, acculturation, behavioral intentions, and risk perception among Asian American college women - Nguyen, Hong V. (Journal of family violence, 2024)
Purpose: Partner violence (PV) among Asian American women is a significant problem, with a reported lifetime prevalence of 16–55% in this population. Sociocultural values, such as loss of face and acculturation, are associated with differences in how Asian American women respond to PV, such as being less likely to disclose their victimization and more likely to remain in an abusive relationship. The purpose of the present study was to examine the impact of cultural factors on in-the-moment behavioral intentions, risk perception, and perceived likelihood of staying in the abusive relationship among Asian American college women. Method: Participants (N = 324) were presented with a progressively threatening PV vignette. We tested three path models, each assessing the associations among loss of face, acculturation, current and future risk perception, perceived likelihood of staying in the relationship, and one of three behavioral intentions (soothe, escape, or escalate/resist). Results: Depending on time and context, loss of face may be a risk factor, whereas acculturation may be a protective factor impacting Asian American college women’s behavioral intentions and risk perception of PV. Conclusion: This is the first study to examine impact of sociocultural variables on multiple in-the-moment behavioral intentions and risk perceptions of Asian American college women in response to PV. Our findings can inform campus-wide PV prevention and intervention efforts for Asian American college women.